Preparing for (life after) death: Advance care directives and cyclic temporalities - Zivkovic, Tanya (The Australian journal of anthropology, 2019)
This paper explores the disjuncture between medico-legal trajectories of living and dying, in which lives start and stop, and the cyclic comings and goings of Buddhist and Hindu bodies. Drawing on fieldwork with Buddhist and Hindu communities in Adelaide, South Australia, I attend to the multiple temporalities that become implicated in end-of-life decision-making about how and when a person may die. Thus, I reorient advance care planning from the linear projection of a single life towards cyclic considerations of the life course. In regarding life and death as ongoing I make space for temporalities of living and dying that run counter to public policy instruments, which focus on an irrevocable, yet calculable, end to life. I demonstrate how advance care planning processes and documents that construct the life course as advancing in a singular, linear and predictable trajectory overlook the multiple temporalities and directions that lives and deaths may take.